2021
DOI: 10.1007/s40475-021-00245-2
|View full text |Cite
|
Sign up to set email alerts
|

Refugee Health During COVID-19 and Future Pandemics

Abstract: Purpose of Review This commentary summarizes recent literature pertaining to healthcare challenges and needs during the current pandemic among refugees and asylum seekers residing in a host country. We conducted a literature review to identify barriers to shielding these structurally marginalized populations from the impact of the COVID-19 pandemic. Recent Findings Many populations, including refugees, migrants, and asylum seekers, endure structural vulnerabilities in refugee camps and during their resettlemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 29 publications
(34 reference statements)
2
23
0
1
Order By: Relevance
“…Yet, despite increasing evidence about COVID-19 and its spread globally, few studies about the direct and indirect effects of the virus in humanitarian and forced displacement settings exist. Articles about refugee populations published so far include modeling studies estimating the number of cases and the role of non-pharmaceutical measures to control the spread of the disease [ 1 , 6 , 9 , 10 ]; reviews of context-specific vulnerabilities and possible impacts in conjunction with appeals for action and integration of refugees in national health responses [ 11 , 12 , 13 ]; and assessments of knowledge and attitude regarding COVID-19 [ 14 , 15 ]. One qualitative study reported on the impact of COVID-19 on utilization and access to maternal services among eleven refugee women in urban Kenya [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, despite increasing evidence about COVID-19 and its spread globally, few studies about the direct and indirect effects of the virus in humanitarian and forced displacement settings exist. Articles about refugee populations published so far include modeling studies estimating the number of cases and the role of non-pharmaceutical measures to control the spread of the disease [ 1 , 6 , 9 , 10 ]; reviews of context-specific vulnerabilities and possible impacts in conjunction with appeals for action and integration of refugees in national health responses [ 11 , 12 , 13 ]; and assessments of knowledge and attitude regarding COVID-19 [ 14 , 15 ]. One qualitative study reported on the impact of COVID-19 on utilization and access to maternal services among eleven refugee women in urban Kenya [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the pandemic, the scientific community has warned about the differential impact of COVID-19 in diverse populations, in terms of clinical and socioeconomic outcomes. Scientists, as well as international bodies and organisations, have drawn attention to the need to protect and include migrants in national responses to the pandemic [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the model can be applied to other communities to better understanding the spread of the virus with the time evolution considering the immigration from other countries. This model might be applied to mitigate the COVID-19 spread associated with uncontrolled international immigration as it is now rising globally [ 25 ]. Indeed, our study pointed out the significant impacts of the undocumented worker who could be COVID-19 carriers and this could bring a new wave of COVID-19 to a country in which the immigration control measures are compromised.…”
Section: Discussionmentioning
confidence: 99%